URBAN VIOLENCE AND HOMICIDES RELATED TO DRUG TRAFFICKING: AN ANALYSIS OF THE VULNERABILITY MARKERS OF INJUNCTIONS FROM THE PERSPECTIVE OF HUMAN RIGHTS IN PIAUÍ (Reflection and Critique Law Magazine, 2023)
This article aims to analyze the violence and homicides generated by drug trafficking, focusing on the State of Piauí, based on the vulnerability markers of inmates, in terms of Human Rights. Drug trafficking generates numerous consequences for society, including urban violence and part of the homicides practiced in Brazil, a determining factor for this social stir is the socioeconomic condition of some young people, who end up being more easily involved by drug trafficking. As for the methodology, it is a qualitative, bibliographic and documentary research, in which the method used is the hypothetical-deductive one, in which conjectures are raised and, finally, consequences are deduced. For data collection, research was carried out in jurisprudence, books, specialized articles and statistics publishedby government agencies. As a result, it was observed that drug trafficking is closely linked to urban violence and homicides in the country, especially in Piauí, manifested mainly by the so-called Crime Court, created within each criminal organization in the state.Keywords: drug trafficking; urban violence; homicides; social vulnerability; Piauí.